Generation of cDNA expression libraries enriched for in-frame sequences - Davis, Claytus A. (The National Academy of Sciences of the USA, 1997)
Bacterial cDNA expression libraries are made to reproduce protein sequences present in the mRNA source tissue. However, there is no control over which frame of the cDNA is translated, because translation of the cDNA must be initiated on vector sequence. In a library of nondirectionally cloned cDNAs, only some 8% of the protein sequences produced are expected to be correct. Directional cloning can increase this by a factor of two, but it does not solve the frame problem. We have therefore developed and tested a library construction methodology using a novel vector, pKE-1, with which translation in the correct reading frame confers kanamycin resistance on the host. Following kanamycin selection, the cDNA libraries contained 60–80% open, in-frame clones. These, compared with unselected libraries, showed a 10-fold increase in the number of matches between the cDNA-encoded proteins made by the bacteria and database protein sequences. cDNA sequencing programs will benefit from the enrichment for correct coding sequences, and screening methods requiring protein expression will benefit from the enrichment for authentic translation products.